2015
DOI: 10.1007/s00410-015-1190-z
|View full text |Cite
|
Sign up to set email alerts
|

Diamond resorption features as a new method for examining conditions of kimberlite emplacement

Abstract: kimberlites offering new method to study crystallization conditions of kimberlite magma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The classical view is based on the whole-rock composition of kimberlite rocks and maintains that kimberlites originate from ultramafic/basic and volatile (H 2 O, CO 2 )-rich melts (Price et al, 2000;le Roex et al, 2003;Becker & le Roex, 2006;Kopylova et al, 2007;Mitchell, 2008;Kjarsgaard et al, 2009). Diamond resorption experiments have been used as an indicator of high volatile activity in kimberlite magmas (Fedortchouk et al, 2010;Fedortchouk, 2015). However, these studies did not test these diamond resorption experiments in putative kimberlite magmas, but rather in aqueous solutions.…”
Section: Kimberlite Composition (Current Debate)mentioning
confidence: 99%
“…The classical view is based on the whole-rock composition of kimberlite rocks and maintains that kimberlites originate from ultramafic/basic and volatile (H 2 O, CO 2 )-rich melts (Price et al, 2000;le Roex et al, 2003;Becker & le Roex, 2006;Kopylova et al, 2007;Mitchell, 2008;Kjarsgaard et al, 2009). Diamond resorption experiments have been used as an indicator of high volatile activity in kimberlite magmas (Fedortchouk et al, 2010;Fedortchouk, 2015). However, these studies did not test these diamond resorption experiments in putative kimberlite magmas, but rather in aqueous solutions.…”
Section: Kimberlite Composition (Current Debate)mentioning
confidence: 99%
“…Some microrelief elements are associated with conditions of natural diamond resorption. Orientation of trigons at high pressures was demonstrated to be controlled by two oxygen fugacities (fO 2 ) and process temperature [26] as well as CO 2 (or CO 3 2+ ) content in resorption medium [18,27,28]. Comparison of diamonds resorbed at pressures of 1-3 GPa and 5-6 GPa in media of similar composition did not reveal any fundamental differences between them.…”
Section: Introductionmentioning
confidence: 93%
“…The structure of trigons on natural diamonds can be studied in more detail using atomic force microscopy (AFM). Y. Fedortchouk [28] presented data on the study of trigons on three crystals of diamond from Ekati Diamond Mine kimberlites using AFM. It was found that p. faces.…”
Section: Trigons On Natural Diamondsmentioning
confidence: 99%
“…Also, f/b and p/b trigons have different relationships between their diameter and depth. For example, on the same diamond f/b trigons often have similar diameters but a large range of depths, whereas p/b trigons show a strong positive correlation between their diameter and their depth (Fedortchouk 2015). Experiments conducted at 1-3 GPa and 1150-1350°C suggest that higher CO 2 content in kimberlitic fluids correlates with (1) increasing size and abundance of p/b trigons at the expense of f/b trigons (Fedortchouk 2015;Zhang et al 2015) and also (2) the development of positively-oriented walls inside negative trigons (resulting in truncated trigons).…”
Section: Octahedral Dissolution Featuresmentioning
confidence: 99%